Hybrid processes in experimental animation - Pertíñez López, Jesús; Alonso Valdivieso, Concepción (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The richest experimental animation requires hybrid processes for its production. These processes can derive from different artistic disciplines, from different software, they can be produced with analog or technological means and all of this can be mixed to obtain a new and unique result. In this contribution we make a journey through the evolution of experimental animation and its current development to analyze its narrative, artistic and aesthetic possibilities. In addition, we propose a catalog of techniques that are commonly used in this type of animation and offer new hybrid techniques created by our research group.